Comparison of National Institutes of Health-Chronic Prostatitis Symptom Index with International Index of Erectile Function 5 in Men with Chronic Prostatitis/Chronic Pelvic Pain Syndrome: A Large Cross-Sectional Study in China. (27th July 2015) - Gao, Jingjing; Gao, Pan; Hao, Zongyao; Zhou, Zengrong; Liu, Jihong; Li, Hongjun; Xing, Junping; Zhou, Zhansong; Deng, Chunhua; Deng, Liwen; Wei, Qiang; Zhang, Xiansheng; et al.
Abstract : The purpose of the study is to evaluate the relationship between NIH-CPSI and IIEF-5 in Chinese men with CP/CPPS. A large cross-sectional and multicenter survey was conducted from July 2012 to January 2014. Men were recruited from urology clinics which were located at the five cities in China. All men participated in the survey by completing a verbal questionnaire (consisted of sociodemographics, past medical history, sexual history, and self-estimated scales). The results showed that 1, 280 men completed the survey. Based on the CP/CPPS definition, a total of 801 men were diagnosed as having CP/CPPS. Men with CP/CPPS reported higher scores of NIH-CPSI and lower scores of IIEF-5 than men without CP/CPPS. NIH-CPSI scores were significantly negatively correlated with IIEF-5 scores. The total scores of NIH-CPSI were significantly more strongly correlated with question 5 than other questions of IIEF-5. The total scores of IIEF-5 were significantly more strongly correlated with pain symptoms scores of NIH-CPSI. Strongest correlation was found between QoL impact and question 5 of IIEF-5. The findings suggested that NIH-CPSI scores were significantly negatively correlated with IIEF-5 scores. Strongest correlation was found between QoL impact and question 5 of IIEF-5.